Stress, Sleep and Performance in International and Domestic University Students - Tan, Corinne Pei Yun; Greenwood, Kenneth Mark (Journal of International Students, 2021)
Stress and poor sleep quality are serious and common problems among university students that could have detrimental effects on their academic performance. International students may experience greater difficulty than domestic students because they also need to deal with the challenges associated with moving to a new culture. The present study aims to investigate the relationship between stress (perceived and acculturative), sleep quality, and academic performance by comparing them between international and domestic students. Perceived stress negatively correlates with sleep quality. However, no relationship is found between acculturative stress and sleep quality, between sleep quality and academic performance, and between stress (perceived and acculturative) and academic performance. Differences in perceived stress and sleep quality between international and domestic students are found. Perceived stress is found to be an important factor that requires the university to focus on effective stress management programs that could be useful for achieving better sleep quality.